Child undernutrition is associated with maternal mental health and other sociodemographic factors in low-income settings in Dhaka, Bangladesh - Kazi Muhammad Rezaul Karim; Md Hafizul Islam; Tasmia Tasnim; Sumaiya Akter (PLoS ONE, 2025)
Background Maternal mental health and other underlying factors might affect a child’s nutritional status. This study assesses child undernutrition and its associated characteristics, including maternal mental health, in low-income settings in Dhaka, Bangladesh. Methods A community-based cross-sectional study was conducted among 397 lactating mothers with children aged 6–23 months from low-income settings in Dhaka. Anthropometric measurements were taken following standard protocols, and Z-scores for weight-for-age, height-for-age, and BMI-for-age were calculated. Maternal depression and anxiety were assessed using the Patient Health Questionnaire-9 and the Generalized Anxiety Disorder 7-Item Scale, respectively. The child feeding index was developed based on breastfeeding, dietary diversity, and meal frequency. Multivariate logistic regression models explored the relationship between child undernutrition and maternal mental health and other risk factors. Results In low-income regions of Dhaka, the prevalence was 31.9% for stunting, 14.0% for wasting, and 24.1% for underweight children. Approximately half of the mothers experienced depression (55%) and anxiety (50%). High maternal depression levels were associated with increased odds of stunted (AOR = 1.80, 95% CI = 1.10–2.94, p < 0.05) and wasted (AOR = 2.70, 95% CI = 1.38–5.28, p < 0.05) children. Similarly, anxiety was linked to a higher risk of underweight children (AOR = 1.77, 95% CI = 1.04–3.11, p < 0.05). Female children had approximately twice the risk of stunting than boys (AOR = 2.13, 95% CI = 1.32–3.44, p < 0.01). Younger maternal age also doubled the risk of stunting (AOR = 1.97, 95% CI = 1.20–3.22, p < 0.01). Low adherence to a feeding index increased the odds of stunting (AOR = 3.21, 95% CI = 1.99–5.16, p < 0.001) and underweight (AOR = 4.20, 95% CI = 2.50–7.07, p < 0.01). Children born to underweight mothers were almost twice as likely to become underweight (AOR = 2.01, 95% CI = 1.01–4.03, p < 0.05) compared to those born to normal/overweight mothers. Conclusion Maternal depression and anxiety adversely affect the nutrition of their children. Sociodemographic factors such as the child’s sex, maternal age, maternal health, and child feeding practices significantly contribute to child undernutrition. Policy initiatives should prioritize maternal mental health and address child undernutrition in these settings.